The Academicaffairs Administration in the Digital Era of the School Administrators Under Khon Kaen Primary Educational Service Areaoffice 1 - Dhammaviriyo (Namthong), Phra Anan; Saikham , Sunthorn; Mahahing, Prachitr (Journal of Modern Learning Development, 2021)
The objectives of this research were: 1) to study the academic affairs administration in the digital era of the school administrators under the KhonKaen Primary Educational Service Area Office 1 and2) to present the guidelines of the academic affairs administration in the digital era of the school administrators under the KhonKaen Primary Educational Service Area Office 1. This study was carried out by means of the mixed method research. The quantitative data collection was conducted with 310samples and the qualitative data was collected from the target group with6 informants. The tools used in this research were the questionnaire and interview form. The statistics used in the data analysis were: Percentage, Mean, Standard Deviation. The research results were as follows: 1.The academic affairs administration in the digital era of the school dministrators under the KhonKaen Primary Educational Service Area Office 1 was rated at a high level of practice in all studied aspects. The study of each aspect in detail reveals that the most practical one was seen in the aspect of learning and teaching processes followed by that of curriculum of the educational institutions, learning and teaching media; while, the least practical aspect was seen in that of evaluation and assessment. When the studied items were ranked, the most rated score was seen in creativity followed by collaboration, technology use, media, reading, writing, arithmetic, critical thinking, morality, cross-cultural thinking and professional skills. 2.The guidelines of the academic affairs administration in the digital era of the school administrators under the KhonKaen Primary Educational Service Area Office 1: 1) is that the curriculum should be revised to be consistent with the 21st century learning. 2) The student-centered teaching and learning, and Active Learning should be managed. 3) modern teaching media through,digital learning platforms and 4) A variety of assessment methods, a tool for improving quality within the school should be used more effectively.